2020
DOI: 10.3390/e22111195
|View full text |Cite
|
Sign up to set email alerts
|

VIP-2 —High-Sensitivity Tests on the Pauli Exclusion Principle for Electrons

Abstract: The VIP collaboration is performing high sensitivity tests of the Pauli Exclusion Principle for electrons in the extremely low cosmic background environment of the underground Gran Sasso National Laboratory INFN (Italy). In particular, the VIP-2 Open Systems experiment was conceived to put strong constraints on those Pauli Exclusion Principle violation models which respect the so-called Messiah-Greenberg superselection rule. The experimental technique consists in introducing a direct current in a copper conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In recent years, a more realistic diffusion random walk model has been developed [22] already employed in open and closed systems [23,24], where the electron-atom interactions in copper occur with a characteristic time τ = 3.3 × 10 −17 s, also taking into account phonons and lattices irregularities. Within this model, the PEP is tested considerably more times with respect to the simple diffusion model.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a more realistic diffusion random walk model has been developed [22] already employed in open and closed systems [23,24], where the electron-atom interactions in copper occur with a characteristic time τ = 3.3 × 10 −17 s, also taking into account phonons and lattices irregularities. Within this model, the PEP is tested considerably more times with respect to the simple diffusion model.…”
Section: Discussionmentioning
confidence: 99%
“…The VIP-2 experiment at the LNGS is proving world-class upper limits on the PEP violation probability in the open system scenarios [15]. Protected by about 3600 m of waterequivalent shielding of the Gran Sasso d'Italia massif, and by lead and copper walls, the experimental setup employs SDDs, housed in a vacuum chamber and placed around a copper target, where a strong direct current is circulated to provide electrons to test PEP.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of electrons scatterings is replaced with the close encounters with individual atoms, and is shown that every close encounter leads to capture with a probability that is only limited by the PEP violating probability. The mean time between close encounters in copper is found to be τ = 3.3 × 10 −17 s. The time taken by the electron to cross the entire target strip transversely is T = 15 s. It follows a new number of interactions between an electron and the copper atoms N int = T/τ, larger than the one in the scattering scheme (see also [34][35][36][37][38]. This leads to an upper limit on the probability of PEP violation for electrons in copper of:…”
Section: Novel Upper Limit On the Pep Violation Probabilitymentioning
confidence: 98%